Deciphering the evolution of supramolecular nanofibers in solution and solid-state: a combined microscopic and spectroscopic approach. Issue 16 (25th March 2021) - Kundu, Subhankar; Chowdhury, Arkaprava; Nandi, Somen; Bhattacharyya, Kankan; Patra, Abhijit
Abstract : Supramolecular nanofiber evolution in solution and solid-state, including stimuli-responsive reversible interconversion among diverse nanoarchitectures, was probed through a combined spectroscopic and microscopic approach. Abstract : Supramolecular self-assembly of small organic molecules has emerged as a powerful tool to construct well-defined micro- and nanoarchitecture through fine-tuning a range of intermolecular interactions. The size, shape, and optical properties of these nanostructures largely depend on the specific assembly of the molecular building units, temperature and polarity of the medium, and external stimuli. The engineering of supramolecular self-assembled nanostructures with morphology-dependent tunable emission is in high demand due to the promising scope in nanodevices and molecular machines. However, probing the evolution of molecular aggregates from the solution and directing the self-assembly process in a pre-defined fashion are challenging. In the present study, we have deciphered the sequential evolution of supramolecular nanofibers from solution to spherical and oblong-shaped nanoparticles through the variation of solvent polarity, tuning the hydrophobic–hydrophilic interactions. An intriguing case of molecular self-assembly has been elucidated employing a newly designed π-conjugated thiophene derivative (TPAn) through a combination of steady-state absorption, emission measurements, fluorescence correlation spectroscopy (FCS), and electron microscopy. The FCS analysis and microscopy results revealed that the small-sized nanofibers in the dispersion further agglomerated upon solvent evaporation, resulting in a network of nanofibers. Stimuli-responsive reversible interconversion between a network of nanofibers and spherical nanoaggregates was probed both in dispersion and solvent-evaporated state. The evolution of organic nanofibers and a subtle control over the self-assembly process demonstrated in the current investigation provide a general paradigm to correlate the size, shape, and emission properties of fluorescent molecular aggregates in complex heterogeneous media, including a human cell.